Style in fiction : a linguistic introduction to English fictional prose - Leech, Geoffrey N. (Longman, 1981)
Describes the ways in which the techniques of linguistic analysis and literary criticism can be combined, and illuminated, through the linguistic study of literary style, and draws on the prose fiction of the last 150 years to demonstrate the approach.